Factors Affecting Household Expenditure using OLS Method: A Case Study of Ward Number 6 of Sidhalek Rural Municipality, Dhading, Nepal - Acharya, Krishna Prasad (Nepalese Journal of Statistics, 2021)
Background: The role of annual household expenditure is very important to run a family smoothly. It incorporates the total expenditure of a family who is residing in a house for their livelihood. There are different factors associated with annual household expenditure, and the assessment of them and identification of such factors play a vital role in the concerned area. Objective: To identify the most significant factors associated with annual household expenditure using an appropriate statistical model. Materials and Methods: The study based on cross-sectional study design with 168 households from ward number 6 of Sidhalek rural municipality of Dhading district were considered for the analysis. The multiple linear regression model followed by appropriate bivariate analysis was used to identify the significant factors associated with the outcome variable. Results: Number of literate persons of working age (β = 0.018, 95% CI: 0.004 - 0.032), remittance-receiving status (β = 0.093, 95% CI: 0.026 - 0.160), and gender of household head (β = 0.089, 95% CI: 0.023 - 0.155) was significantly associated with the annual household expenditure. The goodness of fit and diagnostics of the fitted model were also performed. Conclusion: The annual household expenditure is significantly higher among those households having more literate persons of working age, headed by a male and receiving remittance. Considerable improvements need to be made towards the improvements on human capital and remittance-receiving status particularly in the rural area of Nepal.